Gendered Leadership Strategies: Where are the Women Police? - Anthony, M.; Dayaram, Kandy (Global Publishing House, 2013)
In Chapter Twelve, Mary Anthony and Kandy Dayaram’s study examined the continued paucity of women police in key senior leadership positions. They mentioned that despite the significant progress made by women in paid employment, they still face difficulties in entering into senior leadership roles. They stressed that a plethora of studies on women in paid employment confirm the slow progress of women in key leadership roles; and that while the media often reports about the rise of women in leadership in the workplace, the reality appears to be in stark contrast. According to Mary Anthony and Kandy Dayaram, there are barriers that curtail a woman’s career growth in the Police Force, an organization that is considered to be gendered.